PUBLIC INVESTMENT IN ELECTRICITY TRANSMISSION INFRASTRUCTURE AND THE ECONOMIC IMPACT ON THE ELECTRICITY SUB-SECTOR IN PERU, PERIOD 2000 – 2020 - Cielo Marina, Pablo (2022)
The objective was to estimate the incidence of public investment in electricity transmission infrastructure on the growth of electricity production in Perú, period 2000 - 2020. For the research, a sample was taken for the period 2000 - 2020 of 126 observations, resulting from the 6 variables and 21 years of historical series. Explanatory models were proposed for electricity production and productivity. Also, access to electricity for rural households and its impact on income. In the first model, the results showed a positive and significant impact, which indicates that if public investment in electricity transmission infrastructure increased by 1%, electricity production increased by 1.35%. In the model related to households, it can be seen that if access to electricity is increased by 1% in rural households, rural economic income increases by 0.89%. The research confirmed that public investment is a mechanism to achieve economic growth.